Factors affecting the maximum outcome payments of social impact bonds - Huan Wang; Naipeng Chao; Jiaxi Chen; Mengqi Chen; Tingting Fu (PLoS ONE, 2025)
As governments globally seek market-based solutions to address complex social challenges, Social Impact Bonds (SIBs) have gained prominence in public policy reforms for their potential to align fiscal accountability with social innovation. SIBs are innovative financial tools designed to fund social projects through outcome-based payments, lower government financial pressure, and increase the efficiency with which social problems are solved. In a SIB, the maximum outcome payment refers to the highest amount the outcome payer is willing to provide, and is one of the key factors attracting investor participation. It is typically calculated as the sum of service costs and fiscal savings. However, the current approach often prioritizes reducing government expenditure, without sufficiently accounting for the risks and interests of investors. This improper formulation of maximum outcome payments may cause financing bottleneck and hinder the sustainable development of SIBs. To achieve a balance between government cost control and investor returns, this paper systematically examines the key factors influencing maximum outcome payments through multiple regression analysis, with a focus on macroeconomic factors and bond characteristics. The results indicate that maximum outcome payments are correlated with inflation, capital raised, and the size of the target population for the SIB. Therefore, when determining maximum outcome payments, issuers should consider not only fiscal savings but also bond characteristics and macroeconomic factors.